The Effect of Market Orientation on Firm Performance in F&B Business Sector: The Role of Supply Chain Integration and Firm Innovativeness - Putri Meisya; Dadang Surjasa (Universitas Airlangga, 2022)
Objective: The purpose of this study is to investigate the impact of market orientation on firm performance, as well as the roles of supply chain integration and firm innovativeness in mediating the relationship in the food and beverage sector, micro, small-medium enterprises (MSMEs) in Bekasi Regency Indonesia. Design/Methods/Approach: This study conducts the analyses based on 150 samples that were obtained through questionnaires. To analyze the data, this study employs Partial Least Square Structural Equation Modeling (PLS-SEM) using SmartPLS 3. Findings: The results of this study indicate that market orientation and firm innovativeness have a positive and significant effect on firm performance. Supply chain integration has a positive and insignificant effect on firm performance. Firm innovativeness has a positive and significant effect on firm performance. Supply chain integration is not significant in mediating the relationship between market orientation and firm performance. Firm innovativeness is significant in mediating the relationship between market orientation and firm performance. Originality: This study Contributes to enriching research of firm innovativeness and supply chain integration on MSMEs in Indonesia